Determinant factors influencing organic food purchase intention and the moderating role of awareness: A comparative analysis. (January 2018) - Asif, Muhammad; Xuhui, Wang; Nasiri, Alireza; Ayyub, Samia
Highlights: The study compares the organic behavior of consumers in Pakistan, Turkey and Iran. Further the study also explains the role of awareness in purchase intention. The results of the study vary from country to country. The study establishes the role of awareness in organic food purchase intention. It also guides the policy makers of each country to switch to organic farming. Abstract: The study is comparative in nature and focuses on understanding the factors that affect the purchase intention of organic food in three countries: Pakistan, Turkey and Iran. The study also endeavors to explain the role of awareness as a moderating variable in organic food purchase intention. The data employed in this study was collected from Pakistan, Turkey and Iran using a structured questionnaire. A total of 271 responses from Pakistan, 245 responses from Turkey and 220 responses from Iran were obtained and analyzed using structural equation modeling. The results of the study vary from country to country, but attitude and health consciousness are found to be better predictor organic food purchase intention. The awareness of consumers moderates positively in the intention to purchase of organic food. The relationship of the subjective norms, perceived behavior control and environment concern with intention to purchase vary across different contexts. Current study establishes the role of awareness in the organic food purchase intention which is found to be missing in the literature. Secondly, the study is comparative in nature and compared the behavior of consumers across Pakistan, Turkey and Iran. Current study also guides the policy makers of these countries to switch to organic farming, which will indeed be beneficial for the environment and health, and also a lucrative business because consumer's intentions coincide. Furthermore, the study provides a clear guideline for the practitioners to have an effective marketing strategy in three different countries by exploring the major motivators of organic food purchase intention in each country.